2019
DOI: 10.1111/srt.12664
|View full text |Cite
|
Sign up to set email alerts
|

Tattoos and skin barrier function: Measurements of TEWL, stratum corneum conductance and capacitance, pH, and filaggrin

Abstract: Background Initially after tattooing, the skin barrier function is broken. However, the long‐term impact of clinically healed tattoos on this has never been studied. The aim was to investigate the long‐term effect on the skin barrier function in normal tattoos and examples of tattoos with chronic inflammatory complication. Methods Participants were recruited from the “Tattoo clinic” of the Dermatological Department on Bispebjerg Hospital in Denmark, where patients with complicated tattoo reactions are treated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Norrelet et al found no differences in TEWL and pH values between non-tattooed and tattooed skin in 28 tattoos. Similarly, they found higher capacitance on tattooed skin [ 17 ], in agreement with the higher SCH values on tattooed skin observed in our study. Skin barrier disruption is observed after needle injury micro-traumatisms, which is shown by the slight increases in TEWL observed in our report.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Norrelet et al found no differences in TEWL and pH values between non-tattooed and tattooed skin in 28 tattoos. Similarly, they found higher capacitance on tattooed skin [ 17 ], in agreement with the higher SCH values on tattooed skin observed in our study. Skin barrier disruption is observed after needle injury micro-traumatisms, which is shown by the slight increases in TEWL observed in our report.…”
Section: Discussionsupporting
confidence: 93%
“…To the best of our knowledge, only one previous study has compared skin homeostasis parameters between permanent tattoos and non-tattooed skin [ 17 ]. Norrelet et al found no differences in TEWL and pH values between non-tattooed and tattooed skin in 28 tattoos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Only measurements after the twentieth intervention showed significantly higher TEWL values for the scratched versus the friction forearm. 46 Norreslet et al 47 studied how a permanent skin alteration, (i.e., a tattoo), affected local TEWL values. Twenty-six subjects were included that had a total of 28 tattoos at least 1 year of age; subjects had to have a clear area of skin on the contralateral portion of the body to be used as a control for inclusion in the study.…”
Section: Skincare and Skin Interventionsmentioning
confidence: 99%
“…In this study, we performed the RNA‐sequencing (RNA‐seq) method to explore the transcriptional changes of key genes and pathways involved in skin barrier recovery using the biopsies treated after adhesive tape‐stripping (ATS). The detailed methods are shown in the Data 3–5 …”
Section: Figurementioning
confidence: 99%